Nurse prescribing right: a bibliometric analysis - Wang, Yingying; Jia, Ruixiao; Gu, Su; Wang, Zihan; Zhu, Liqun; Ma, Shaoyong (Frontiers in Medicine, 2025)
BackgroundThe concept of nurse prescribing rights is undergoing rapid evolution, and there is increasing interest in academic circles regarding research on this topic.ObjectiveThis study aims to conduct a comprehensive bibliometric analysis of nurses’ prescribing rights to understand the research background, emerging trends, and relevant academic impacts in this field, so as to provide valuable insights for the formulation of health policies and the promotion of more equitable and efficient healthcare services.MethodsWe conducted a bibliometric analysis of the articles on nurses’ prescribing rights from the establishment of the database until 6 December 2023. The data used were collected from the Web of Science Core Collection database. We carried out a bibliometric analysis with the aim of determining the overall research directions and trends of the currently published literature. At the same time, we sought to identify the most productive and influential countries/regions, institutions, journals, authors, research categories, keywords, and articles in the field of nurses’ prescribing rights. We used software such as VOSviewer and CiteSpace, as well as the tool Biblioshiny to collect and analyze the data, with a focus on conducting analysis and visualization.ResultsA total of 555 papers were obtained from 848 institutions in 44 countries. These papers were published in 237 journals and were written by 1,902 authors. From 2018 to 2023, there was a significant increase in the number of publications, accounting for 40.54% (225/555) of the total. The United States and the University of Reading have published the largest number of papers on this topic. The United Kingdom has the highest frequency of citation and cooperation. Out of the 555 publications, six clusters were formed, focusing on Nursing Practitioners, Primary Care, and Education. The research frontier mainly revolves around Buprenorphine and Opioid.ConclusionThis study provides a comprehensive overview of the research progress in the field of nurse prescribing rights. Through statistical analysis and network visualization, we have identified the background, trends, and key topics in this research area. Our findings indicate that the prescribing rights of nurses have experienced rapid development in recent years and have played a crucial role in addressing the shortage of primary medical resources. The insights gained from this study can serve as a valuable reference and provide guidance for future research in this field.